Cytomegalovirus Pneumonia in Hematopoietic Stem Cell Recipients. (July 2014) - Travi, Giovanna; Pergam, Steven A.
Cytomegalovirus (CMV) is a frequently encountered infection following hematopoietic cell transplantation, and tissue invasive pneumonia is a dreaded complication of the virus in this population. In this review of CMV pneumonia, we address epidemiology, pathogenesis, diagnostics, current therapy, and strategies to prevent the development of CMV. We also review emerging treatment and prevention options for this challenging disease.